Double-blind, placebo-controlled first in human study to investigate an oral vaccine aimed to elicit an immune reaction against the VEGF-Receptor 2 in patients with stage IV and locally advanced pancreatic cancer - Niethammer, Andreas Gerhard; Mikus, Gerd; Knebel, Phillip; Hohmann, Nicolas; Leowardi-Bauer, Christine; Beckhove, Philipp; Akhisaroglu, Mustafa; Ge, Yingzi; Grenacher, Lars; Büchler, Markus W.; Koch, Moritz; Weitz, Jürgen; et al. (BMC cancer, 2012)
The investigational oral DNA vaccine VXM01 targets the vascular endothelial growth factor receptor 2 (VEGFR-2) and uses Salmonella typhi Ty21a as a vector. The immune reaction elicited by VXM01 is expected to disrupt the tumor neovasculature and, consequently, inhibit tumor growth. VXM01 potentially combines the advantages of anti-angiogenic therapy and active immunotherapy.